Partisipasi Politik Elit Desa dalam Pembentukan Kabupaten Bandung Barat (Tahun 1998-2007) - KARTIKA RETNO PRATIWI (Universitas Sumatera Utara, 2010)
This study analyses about the role and participation of village elite to make new regional gov-ernment administration (Kabupaten). Focused on Kabupaten Bandung Barat this study using the elite approach to analyses who is the main actor inside this agenda. The result seen that village elite (bureaucratic, entrepreneurs) have three method to make the new regional govern-ment administration especially at case of Kabupaten Bandung Barat as a new regional enfold-ment. In this case firstly village elite using his resources like knowledge, influence, and role to show this agenda. Secondly village elite making a link with government of Jawa Barat do the lobby to get supporting from regional government (Gubernur). Thirdly village elite making a networking with elite at center government to make this agenda successful. Without the role and participation of village elite, this agenda will be failed. So, in politics the role and political par-ticipation of elite is significant variable.Keywords: Political elite, Regional enfoldment, Political participation.